Examining the influence of religion and spirituality on mental health help-seeking among Nigerians: A scoping review protocol - Chukwu, A. (Journal for the Study of Spirituality, 2025)
This protocol examines the influence of religious and spiritual beliefs on mental health help-seeking patterns and behaviours among Nigerians; (a) to understand how these beliefs influence attitudes towards mental health illness and services utilisation; (b) to identify and evaluate gaps in the existing literature and (c) to make suggestions for future research. The protocol for this scoping review is in accordance with the Arskey and O’Malley framework for scoping reviews. Studies relevant to the scope of the review will be identified through a systematic search of relevant databases including CINAHL, PubMed, EbscoHost, ProQuest, PsychInfo, Web of Science and Scopus. Religion and spirituality-themed alternative mental healthcare is commonplace in countries such as Nigeria with some studies suggesting this as a first point of contact for individuals experiencing mental health difficulties. However, the influence of these alternative methods on mental health help-seeking and service utilisation remains under researched. This review is expected to impact the future design and delivery of mental health services to better equip them in the provision of culturally competent mental health services. An understanding of the influence of religion and spirituality on mental health help-seeking choices can increase trust and service utilisation within the Nigerian community.